Kiai Rifa'i dan Syiar Islam di Kabupaten Sidoarjo 1965 - 2002 - Alim Suwara; Nyong Eka Teguh Iman Santosa; Amiq (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2022)
Abstract: This article examined the role of K.H. Ahmad Rifa'i in his preaching in Gedangan Village, Gedangan Subdistrict, Sidoarjo Regency, 1965 - 2002. The data were compiled using historical research methods, namely heuristics (data collection), verification (criticism of data), interpretation (interpretation), and historiography (history writing). By using the role theory this study concluded that (1) K.H. Rifa'i was born in the village of Diwek Jombang from the couple Kyai Mahali and Nyai Hj. Khanna, he was born in 1912 AD (2) The condition of the Gedangan community at that time still showed the influence of communists and abangans so that some people still carried out religious rituals such as placing offerings in certain places (3) The role of the Kyai Rifa in broadcasting Islam in Gedangan is being able to change the habits of the Gedangan people who were initially dominated by communist groups and Abangan Muslims into societies that behave according to the guidance in Islam. Keywords: Kiai Rifa’i, Gedangan, Sidoarjo, islamic da’wa,